2010
DOI: 10.1002/pi.2883
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyesters based on 1,1,1‐[bis(4‐hydroxyphenyl)‐4′‐pentadecylphenyl]ethane

Abstract: Aromatic polyesters are of considerable interest because of their excellent mechanical properties, chemical resistance and thermal stability. However, most aromatic polyesters are difficult to process due to their high glass transition temperatures coupled with their insolubility in common organic solvents. The present article describes a series of organosoluble polyesters and copolyesters based on 1,1,1‐[bis(4‐hydroxyphenyl)‐4′‐pentadecylphenyl]ethane. A series of new aromatic polyesters containing pendant pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The bisphenol monomers viz ; 1,1,1‐[bis(4‐hydroxyphenyl)‐4′‐pentadecylphenyl]ethane (BHPE) and 1,1‐bis(4‐hydroxyphenyl)‐3‐pentadecylcyclohexane (BHPC) were synthesized starting from cashewnut shell liquid (CNSL) using procedure described in our previous work. 34, 37, 39, 40 The 4,4′‐difluorobenzophenone (DFB) and 1,3‐bis(4‐fluorobenzoyl)benzene (BFB) (Aldrich, USA) were recrystallized from toluene before use. Anhydrous potassium carbonate (S.D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bisphenol monomers viz ; 1,1,1‐[bis(4‐hydroxyphenyl)‐4′‐pentadecylphenyl]ethane (BHPE) and 1,1‐bis(4‐hydroxyphenyl)‐3‐pentadecylcyclohexane (BHPC) were synthesized starting from cashewnut shell liquid (CNSL) using procedure described in our previous work. 34, 37, 39, 40 The 4,4′‐difluorobenzophenone (DFB) and 1,3‐bis(4‐fluorobenzoyl)benzene (BFB) (Aldrich, USA) were recrystallized from toluene before use. Anhydrous potassium carbonate (S.D.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported a series of difunctional monomers containing pendant pentadecyl chain which were utilized for the synthesis of high performance polymers such as aromatic polyesters, polyamides, poly(amideimide)s, and polyimides. 34–38 It was demonstrated that the presence of pendant pentadecyl chains improved the solubility and processability of these polymers and provided a large temperature difference between the glass transition temperature and the initial decomposition temperature. In continuation of our ongoing‐efforts to synthesize processable high performance polymers, we wish to report herein synthesis of poly(ether ether ketone)s (PEEKs) and poly(ether ether ketone ketone)s (PEEKKs) containing pendant pentadecyl chains by nucleophilic polycondensation of each of the two bisphenols viz , 1,1,1‐[bis(4‐hydroxyphenyl)‐4′‐pentadecylphenyl]ethane (BHPE) and 1,1‐bis(4‐hydroxyphenyl)‐3‐pentadecyl cyclohexane (BHPC) with commercially available aromatic dihalide monomers viz ; 4,4′‐difluorobenzophenone (DFB) and 1,3‐bis(4‐fluorobenzoyl)benzene (BFB).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that polymers having long flexible side chains crystallize into layered structures in which the main chains come together to form backbone layers and the side chains to form a separate crystal region 31–35, 38, 43–45. X‐ray diffractograms of polyhydrazides and poly(1,3,4‐oxadiazole)s displayed presence of sharp reflection peak in the small‐angle region at around 2θ = ∼ 3°.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported a series of soluble and processable high performance polymers containing pendant pentadecyl chains starting from (CNSL). It was demonstrated that, the pentadecyl chains acts as an internal plasticizers and hence aids in improved processability and simultaneously imparts the solubility characteristics to the resulting polymer 33–38. In continuation with our ongoing efforts to obtain polymers with improved solubility, we wish to report herein synthesis of a series of new poly(1,3,4‐oxadiazole)s containing flexibilizing ether linkages and pentadecyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing with our efforts towards processable high performance polymers containing pentadecyl chains, [22][23][24][25][26][27][28][29][30] we report herein the synthesis of a new bisphenol, viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) starting from cashew nut shell liquid (CNSL). We also report the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50:50 mol %) to form a series of polyesters.…”
Section: Introductionmentioning
confidence: 99%